Analysis Of The Transmission System In A 2010 Honda Beat Electric Motorcycle - Gafur, Abdul; Imran, Imran; Vebritasari, Vebritasari (ABEC Indonesia, 2024)
With the advancement of technology and the growing awareness of environmental protection, electric motorcycles arebecoming increasingly popular as eco-friendly alternatives to conventional motor vehicles. The modification of the 2010 HondaBeat is one such electric motorcycle model that has gained public attention due to its attractive design and reasonably goodperformance. However, despite the rising popularity of electric motorcycles, there are still some technical aspects that needfurther analysis to ensure optimal performance. One important component in a motorcycle is the transmission system. Thetransmission system functions to convert engine power into motion at the drive wheel. The cause of slipping that occurs in the2010 Honda Beat electric motorcycle is overly loose tension. In the 2010 Honda Beat electric motorcycle, the transmissionsystem has been changed from a belt drive transmission to a sprocket transmission system, with a ratio of 15 teeth on the frontsprocket and 32 teeth on the rear sprocket, resulting in a sprocket ratio of 2.128. The chain speed is 7.7 m/s with 76 chain links ora length of 84.22 cm. The transmission system on this electric motorcycle uses a number 40 single-chain drive.